The assessment of the rationality of the pharmacotherapy of acute respiratory viral infection in the outpatient practice: uk. - Balitska, O. P.; Hryhoruk, Yu. M.; Artemchuk, M. A.; Zlahoda V. S., V. S. (Social Pharmacy in Health Care, 2021)
Acute respiratory viral infections (ARI) and influenza occupy a leading place in the structure of the overall morbidity of the population in most countries. Aim. To assess the rational prescription of drugs for etiotropic therapy of ARI in the outpatient practice. Materials and methods. The following materials for research were used: case histories; treatment sheets; the Unified clinical protocol of primary care for adults and children “Acute respiratory infections”; data of the State Formulary of Medicines as of January 2021; the Register of wholesale prices; the weekly “Apteka” (Pharmacy). The methods of retrospective, descriptive, frequency, and VEN-analysis were applied. Results. According to the research results, using patient histories, it was found that family doctors prescribed 67 drugs by trade names. For etiotropic therapy, 24 drugs were used; it was 37 % of the total number, and 63 % – for symptomatic therapy. Such drugs as Amizon, Aflubin, Amixin, Resistol, Umkalor were for etiotropic therapy (more than 5 prescriptions). None of these drugs is included in the State Formulary of Medicines and the Unified clinical protocol for the treatment of influenza and SARS. Thus, these drugs are without the proven efficiency, safety and cost-effective use. Conclusions. The study conducted has shown that the drugs prescribed most often do not have an evidence base of efficacy and safety; none of the most frequently prescribed drugs is included in the State Formulary of Medicines and the Unified clinical protocol. A direct relationship between an increase in the number of prescriptions and an increase in price has been proven. Key words: acute respiratory viral infections; influenza; frequency analysis; VEN-analysis; family doctor.